2006
DOI: 10.1071/ar04137
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the impact of perennial phases on average leakage from farming systems in south-western Australia

Abstract: Rising watertables and dryland salinity in southern Australia are due to excess groundwater recharge after the replacement of native vegetation by annual crops and pastures. The inclusion of perennial plants into agricultural systems has been proposed as a possible method of recharge reduction, through the creation of a buffer (extra water storage capacity generated by the perennial in comparison with an annual crop or pasture). However, the role of perennial phases under conditions of highly episodic leakage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
0
19
1
2
Order By: Relevance
“…This causes salinity when the groundwater rises and brings to surface dissolved salts that hinder plant growth. Recharge values for annual crops or pastures and trees on each LMU were estimated using a model of water leakage for agricultural areas, LBUM (Ward 2006). Different soils have different properties which affect their recharge rate.…”
Section: Groundwater Recharge and Salinitymentioning
confidence: 99%
“…This causes salinity when the groundwater rises and brings to surface dissolved salts that hinder plant growth. Recharge values for annual crops or pastures and trees on each LMU were estimated using a model of water leakage for agricultural areas, LBUM (Ward 2006). Different soils have different properties which affect their recharge rate.…”
Section: Groundwater Recharge and Salinitymentioning
confidence: 99%
“…Much of the environmentally degrading deep drainage that occurs is attributable to episodic rainfall events occurring outside the normal growing season (Black et al 1981;Asseng et al 2001;Ward 2006). However, the experimental sites in this research received few such episodic rainfall events.…”
Section: Discussionmentioning
confidence: 77%
“…The superior ability of lucerne (Medicago sativa L.) to dry the soil profile in a range of environments is well documented (Christian 1977;Lolicato 2000;Latta et al 2001;Ridley et al 2001a;Brown et al 2005;Bell et al 2006;Fillery & Poulter 2006;Sandral et al 2006;Ward 2006). Rarely has any pasture species been reported to exceed lucerne in its capacity to dry the soil profile, although occasionally an alternative species is reported to have achieved the same level of drying as lucerne.…”
Section: Introductionmentioning
confidence: 97%
“…The length of the lucerne phases in the rotations containing perennial pasture in Sections 4.1-4.4 are sufficient to prevent the development of dryland salinisation on the field of interest. This is identified through the calculation of mean recharge over the last century for each rotation using the Leakage-Buffer model (Ward 2006) (data not shown). Furthermore, Doole (2007) identified that, if the value of lucerne phases for weed management is not considered and the only effect of salinisation is the loss of agricultural production, perennial pasture is only profitable to adopt for salinity prevention if a saline water table is less than 3.5 m from the soil surface.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, crop yield declines if insufficient weed control is attained. Continued reliance on shallow-rooted annual crops and pastures in rotations has also encouraged the onset of dryland soil salinisation by allowing a higher proportion of rainfall to recharge saline water tables, relative to that occurring under native vegetation (Pannell and Ewing 2006;Ward 2006).…”
Section: Introductionmentioning
confidence: 99%